Intuitive Practitioner: on the value of not always knowing what one is doing - Atkinson, Terry; Claxton, Guy (Berkshire Open University Press, 2003)
Much of the time, experienced professionals in both education and other fields cannot explain what they are doing, or tell you what they know; and students cannot articulate their learning. Yet professional development and practice are often discussed as if conscious understanding and deliberation are of the essence. The Intuitive Practitioner tackles this apparent paradox head on, and explores the dynamic relationship between reason and intuition in the context of professional practice. Focusing mainly on the professional world of the teacher, but with illustrative discussions of medical and business practice, the contributors delicately unpick the vexed and neglected nature of intuition, and demonstrate the vital role it plays in the development of professional judgement and expertise.